Association between pre‐admission anticoagulation and in‐hospital death, venous thromboembolism, and major bleeding among hospitalized COVID‐19 patients in Japan. Issue 6 (7th April 2022) - Adomi, Motohiko; Kuno, Toshiki; Komiyama, Jun; Taniguchi, Yuta; Abe, Toshikazu; Miyawaki, Atsushi; Imai, Shinobu; Morita, Kojiro; Saito, Makoto; Ohbe, Hiroyuki; Kamio, Tadashi; Tamiya, Nanako; et al.
Abstract: Purpose: The coagulation activation leads to thrombotic complications such as venous thromboembolism (VTE) in patients with coronavirus disease‐2019 (COVID‐19). Prophylactic anticoagulation therapy has been recommended for hospitalized COVID‐19 patients in clinical guidelines. This retrospective cohort study aimed to examine the association between pre‐admission anticoagulation treatment and three outcomes: in‐hospital death, VTE, and major bleeding among hospitalized COVID‐19 patients in Japan. Methods: Using a large‐scale claims database built by the Medical Data Vision Co. in Japan, we identified patients hospitalized for COVID‐19 who had outpatient prescription data at least once within 3 months before being hospitalized. Exposure was set as pre‐admission anticoagulation treatment (direct oral anticoagulant or vitamin K antagonist), and outcomes were in‐hospital death, VTE, and major bleeding. We conducted multivariable logistic regression analyses, adjusting for a single summarized score (a propensity score of receiving pre‐admission anticoagulation) for VTE and major bleeding, due to the small number of outcomes. Results: Among the 2612 analytic patients, 179 (6.9%) had pre‐admission anticoagulation. Crude incidence proportions were 13.4% versus 8.5% for in‐hospital death, 0.56% versus 0.58% for VTE, and 2.2% versus 1.1% for major bleeding among patients with and without pre‐admission anticoagulation, respectively. Adjusted odds ratios (95% confidence intervals) were 1.25 (0.75–2.08) for in‐hospital death, 0.21 (0.02–1.97) for VTE, and 2.63 (0.80–8.65) for major bleeding. Several sensitivity analyses did not change the results. Conclusions: We found no evidence that pre‐admission anticoagulation treatment was associated with in‐hospital death. However, a larger sample size may be needed to conclude its effect on VTE and major bleeding.